2016
DOI: 10.1520/gtj20150151
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration Column for Studying the Lateral Swell Behavior of Expansive Clay

Abstract: International audienceInfiltration column is usually used to investigate the hydro-mechanical processes in unsaturated expansive clay. In this test, the moisture transfer is often monitored along the column during water infiltration using suction or water content probes. Nevertheless, the lateral swelling pressure developed is rarely considered. This paper describes an infiltration column for studying the lateral swell behavior of expansive clay. The column consists of a rigid cell ensuring the constant-volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The investigated material is MX-80 bentonite mixture with a mass base proportion of 80% high-density pellets and 20% powder. MX-80 bentonite presents a high montmorillonite content (80%), liquid limit 420 -560%, plastic limit 62%, and density of particles 2.77 Mg/m 3 [9]. High-density bentonite pellets (approximately 7 mm in diameter) have been produced by compaction to a dry density ȡ d = 1.99 Mg/m 3 .…”
Section: Materials Description and Oedometer Testmentioning
confidence: 99%
“…The investigated material is MX-80 bentonite mixture with a mass base proportion of 80% high-density pellets and 20% powder. MX-80 bentonite presents a high montmorillonite content (80%), liquid limit 420 -560%, plastic limit 62%, and density of particles 2.77 Mg/m 3 [9]. High-density bentonite pellets (approximately 7 mm in diameter) have been produced by compaction to a dry density ȡ d = 1.99 Mg/m 3 .…”
Section: Materials Description and Oedometer Testmentioning
confidence: 99%
“…Recent studies have observed distinct anisotropic characteristics between vertical and horizontal swelling of intact expansive soil specimens [18][19][20]. From the microstructure analysis, flaky clay particles within expansive soils are inclined to orient horizontally after compaction; this preferred orientation phenomenon becomes more apparent with an increase in static pressure, consequently leading to significant differences in swelling behavior [21].…”
Section: Introductionmentioning
confidence: 99%